Research progress on coronary slow flow or no-reflow of coronary heart disease undergoing percutaneous coronary intervention surgery - Mengdi Wang; Min Zeng (Guoji laonian yixue zazhi)
Coronary heart disease (CHD), a prevalent cardiovascular disorder, poses a significant threat to human health.Particularly, ST-segment elevation myocardial infarction (STEMI) is associated with a higher mortality rate.Timely and effective revascularization of the culprit vessels is crucial.Percutaneous coronary intervention (PCI) is a preferred and critical treatment modality for STEMI patients, effectively addressing vascular obstruction.However, a subset of patients experiences coronary slow flow (CSF) or no-reflow (NR) postoperatively, which severely impacts their prognosis.This article provides a comprehensive review of the definition, diagnosis, epidemiology, predictive factors, mechanisms, and treatment of CSF/NR, aiming to offer guidance for the clinical management of these complications following PCI in CHD patients.